2015
DOI: 10.1037/a0038548
|View full text |Cite
|
Sign up to set email alerts
|

Referential coding does not rely on location features: Evidence for a nonspatial joint Simon effect.

Abstract: The joint Simon effect (JSE) shows that the presence of another agent can change one's representation of one's task and/or action. According to the spatial response coding approach, this is because another person in one's peri-personal space automatically induces the spatial coding of one's own action, which in turn invites spatial stimulus-response priming. According to the referential coding approach, the presence of another person or event creates response conflict, which the actor is assumed to solve by em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 82 publications
1
18
0
Order By: Relevance
“…Our finding that the cSE is modulated by the type of response mode but not by the type of co-actor suggests that the perceived similarity between both actors can also be induced by procedural aspects of the task, like the way in which action events are delivered, and not only by perceptual features of the event (Sellaro, Dolk, Colzato, Liepelt, & Hommel, 2015). These procedural aspects of the task relating to event production had a stronger impact on joint task performance than the physical appearance or humanness of the interaction partner.…”
Section: Discussionmentioning
confidence: 81%
“…Our finding that the cSE is modulated by the type of response mode but not by the type of co-actor suggests that the perceived similarity between both actors can also be induced by procedural aspects of the task, like the way in which action events are delivered, and not only by perceptual features of the event (Sellaro, Dolk, Colzato, Liepelt, & Hommel, 2015). These procedural aspects of the task relating to event production had a stronger impact on joint task performance than the physical appearance or humanness of the interaction partner.…”
Section: Discussionmentioning
confidence: 81%
“…Perceived similarity between ones' own and other's generated events determines the need to use the spatial dimension as a reference frame. This perceived similarity can be present at a perceptual level, i.e., similarity between the participant's and the co-actor's action effects (Sellaro, Dolk, Colzato, Liepelt, & Hommel, 2015), but it can also exist on more abstract levels such as the similarity in personal relationship between both actors (Stenzel et al). Previous research has indeed shown that both non-social (e.g., a metronome or a Japanese waving cat; Dolk et al, 2013) and social factors such as the friendliness of the co-actor (Hommel, Colzato, & van den Wildenberg, 2009), interdependency (Colzato, de Bruijn, & Hommel, 2012), and social exclusion (Costantini & Ferri, 2013) may modulate the size of the SSE.…”
Section: Ssementioning
confidence: 99%
“…This is in line with the findings reported by Humphreys and Bedford (2011) in frontal patients. According to the referential coding account, a joint action task requires the coding of self-own action (I-go) and other-own action (You-go), especially in a turn-taking response as in the present study (Dolk et al, 2011(Dolk et al, , 2013Hommel, 2009Hommel, , 2011Hommel et al, 2001Liepelt et al, 2011, 2013Prinz, 2015;Sellaro et al, 2015;Stenzel & Liepelt, 2016). In other words, the joint action task induces a response-selection conflict between self-own action and other-own action when a target is presented.…”
Section: Discussionmentioning
confidence: 66%
“…However, the action co-representation account for the joint compatibility effect has recently been challenged (Dittrich, Bossert, Rothe-Wulf, & Klauer, 2017;Dittrich, Dolk, Rothe-Wulf, et al, 2013;Dittrich, Rothe, & Klauer, 2012;Dolk, Hommel, Prinz, & Liepelt, 2013, 2014aDoneva & Cole, 2014;Guagnano, Rusconi, & UmiltĂ , 2010;Hommel, Colzato, & van den Wildenberg, 2009;Klempova & Liepelt, 2015;Liepelt, Wenke, Fischer, & Prinz, 2011;MĂĽller, Brass, KĂĽhn, et al, 2011a;Porcu, Bölling, Lappe, & Liepelt, 2016;Puffe, Dittrich, & Klauer, 2017;Sellaro, Dolk, Colzato, et al, 2015;Stenzel & Liepelt, 2016; see Dolk, Hommel, Colzato et al, 2011, 2014b. One of these recent alternative accounts is the referential coding account (Dolk et al, 2011(Dolk et al, , 2013(Dolk et al, , 2014a, which offers a plausible explanation for modulations of the joint Simon effect in a number of observations, such as group membership (i.e., in-group vs. out-group; MĂĽller, KĂĽhn, van Baaren et al, 2011b) or the presence of a joint Simon effect in presence of nonhuman co-actors (e.g., Japanese waving cat: Dolk et al, 2013) compared with the action co-representation account.…”
Section: Introductionmentioning
confidence: 99%